Empowering householders: Identifying predictors of intentions to use a home energy management system in the United Kingdom. (April 2020) - Whittle, Colin; Jones, Christopher R.; While, Aidan
Abstract: Trials of technologies designed to promote residential demand-side energy management (DSM) have found aggregate levels of load-shifting behaviour and curtailment in energy use. These aggregate data, however, mask considerable differences in people's engagement in DSM at an individual household level. We present the findings of a quantitative exploration of people's intentions to use a home energy management system (HEMS) for residential DSM in the United Kingdom. The technology acceptance model (TAM) was used in conjunction with constructs measuring psychological empowerment and environmental attitudes to explore participants' acceptance of a HEMS to facilitate load-shifting. Findings from a mediation analysis showed perceptions of the usefulness of the HEMS and its ease of use were important predictors of people's intentions to use one. They also highlight a potential conflict between an individual's home energy consumption goals and national DSM goals. The implications of these findings for understanding end-user acceptance of HEMS are discussed. We conclude that seeking opportunities to promote shared, internalised goals for residential DSM may be an avenue for increasing the uptake and use of technologies designed to enable load-shifting (and other energy conservation behaviours) among end-users. Highlights: Acceptance of a home energy management system (HEMS) is explored in a UK sample. Acceptance is explored in the context of load shifting. Psychological empowerment and environmental concern are explored as predictors. Role of sharing national energy reduction targets in HEMS′ acceptance discussed. Implications for smart energy technology acceptance are discussed.